Analysing training in gender-based violence for undergraduate nursing students in Spain: A mixed-methods study. (June 2019) - Maquibar, Amaia; Estalella, Itziar; Vives-Cases, Carmen; Hurtig, Anna-Karin; Goicolea, Isabel
Abstract: Background: Health-care professionals, and nurses especially among them, play an essential role in the health sector's response to gender-based violence. To be able to successfully address this major public health issue they need specific training in the topic. Objective: To analyse training on gender-based violence that nursing students receive at universities in Spain. Design: Mixed-methods approach. Setting: Spain. Methods: Systematic review of public documents followed by in-depth interviews with university lecturers. Results: Eighty per cent (92/115) of nursing training programmes included content regarding gender-based violence. There was great variability in the topics included in the training. Health consequences due to gender-based violence exposure and the role of the health sector in addressing these health consequences were the most frequently included topics. Ethical issues and legislation were the least frequent ones, as these were only dealt with in one and 18 training programmes, respectively. In the qualitative analysis of the interviews, two categories were identified: 'Supportive legislation and supportive lecturers are essential for integrating gender-based violence training' and 'Approach to gender-based violence shapes the contents and the subject in which it is incorporated'. The first category refers to the main drivers for training integration, while the second category refers to how lecturers' perceptions influenced the way in which training was implemented. Conclusions: As many as 80% of the nursing education programmes included specific training in gender-based violence, although with great variability in the contents among the universities. For this study's participants, enacted legislation, and lecturers interested in the topic and in decision-making positions were key drivers for this extensive implementation. The variability observed across universities might be explained by lecturers' different approaches to gender-based violence and the nursing profession.